The Contestation of Interpretational Authority between ʻUlamāʻ and Artificial Intelligence: A Critical Study of AI Epistemology in Quranic Studies - Kutsal van den Berg; Bart Bedner; Martijn Zheng; Philipp Grote; Alisha Shema (Yayasan Albahriah Jamiah Indonesia, 2026)
The development of artificial intelligence in the analysis of religious texts has encouraged its use in Quranic studies, including in the practice of interpretation, which, in turn, raises fundamental epistemological issues in the form of contestation over interpretive authority between ʻulamāʻ as interpretive subjects and AI as a computational system. This issue not only addresses the technical aspects of producing meaning but also challenges the legitimacy of knowledge, sources of epistemic authority, and standards of interpretive validity. To date, studies that systematically formulate the epistemic boundaries and position of AI authority within the epistemological framework of Quranic interpretation are still relatively limited. This study aims to critically and conceptually analyze the epistemology of AI in Quranic studies, thereby confirming the position and limits of interpretive authority between ʻulamāʻ and artificial intelligence. This study employs a qualitative method, drawing on library studies of classical and contemporary interpretation literature, philosophy of science, and critical technology studies, with a philosophical-epistemological and hermeneutic analysis approach. The results of this study indicate that AI operates at the instrumental-operational level by processing textual data, linguistic statistics, and syntactic patterns, without the capacity for intentionality, historical awareness, and normative reflection, which are the epistemic prerequisites for Quranic interpretation. This finding confirms that the epistemic authority of interpretation remains with the ʻulamāʻ due to their involvement in hermeneutic awareness, mastery of scientific traditions, methodological responsibility, and ethical dimensions in the production of meaning. This study also reveals that the uncontrolled integration of AI has the potential to shift the standard of interpretation validity from epistemological considerations to the logic of technological efficiency. In conclusion, this study strengthens the epistemology of contemporary interpretation by formulating a relational framework that positions AI as a limited epistemic tool, rather than as a holder of interpretive authority.